Hormonal control of the shoot stem-cell niche - Zhao, Zhong; Miotk, Andrej; Lohmann, Jan U. (Nature, 2010)
The classic phytohormones cytokinin and auxin play essential roles in the maintenance of stem-cell systems embedded in shoot and root meristems, and exhibit complex functional interactions. Here we show that the activity of both hormones directly converges on the promoters of two A-type ARABIDOPSIS RESPONSE REGULATOR (ARR) genes, ARR7 and ARR15, which are negative regulators of cytokinin signalling and have important meristematic functions. Whereas ARR7 and ARR15 expression in the shoot apical meristem (SAM) is induced by cytokinin, auxin has a negative effect, which is, at least in part, mediated by the AUXIN RESPONSE FACTOR5/MONOPTEROS (MP) transcription factor. Our results provide a mechanistic framework for hormonal control of the apical stem-cell niche and demonstrate how root and shoot stem-cell systems differ in their response to phytohormones.